Rasadā - Brahmabhaṭṭa, Prahlāda (Śrī Lakṣmī Pustaka Bhaṇḍāra, 2004)
Novel, based on the life of Rasda, a fictional woman character.
A novel - Gujarati in Gujarati-Schr
Keywords: Gujarātī-Sprache; Roman; Geschichte 1900-2002